Transformasi PPL-KKN Integratif Menjadi Program Latihan Profesi di Prodi Manajemen Pendidikan Islam - Ulmunir, Misbah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2016)
The implementation of Presidential Decree number 8 year 2012 about Indonesian National Qualification Framework (KKNI) and Act number 14 year 2005 aboutteacher and lecturer, requires reorganization and qualification development of thehigher education institution which run a program for education and administratif stafeducation (LPTK) as well as all instruments within it. Course changing as an academiceffort in the education institution should be designed sistematically by considering theconstitution as well as to accomdate the needs. This research is a qualitatif research usingcareful tracing toward various documents related to the transformation of the courseIntegrative Teaching Experience and Community Service (PPL KKN) into InternshipII in the Faculty of Tarbiyah and education, as well as interview, documentation, andobservation to the transformation process. Researcher used triangulation technique tocheck the data validity. The research shows that the transformation of course IntegrativeTeaching Experience and Community Service (PPL-KKN) into PLP II covers the visionand mision, aim, advantage, outline changes, organiser, implementation mechanism,and evaluation.